Philosophy of Chemistry
VIII, 362 p.
Keywords: This comprehensive volume marks a new standard in scholarship in the still emerging field of the philosophy of chemistry. With selections drawn from a wide range of scholarly disciplines, philosophers, chemists, and historians of science here converge to ask some of the most fundamental questions about the relationship between philosophy and chemistry. What can chemistry teach us about longstanding disputes in the philosophy of science over such issues as reductionism, autonomy, and supervenience? And what new issues may chemistry bring to the forefront now that it has joined physics and biology as a serious topic for philosophical reflection? This newest addition to the prestigious Boston Studies in the Philosophy of Science series marks the true arrival of philosophy of chemistry within the corpus of the philosophy of science.